Social capital, deprivation and self-rated health of residents of Gauteng: a multilevel analysis - Oguttu, James Wabwire (My University, 2020)
Social capital which is defined as resources and benefits derived through connections with others, has been linked to population health. However, few studies of the relationship between social capital and health have been conducted in developing countries. This study investigated the association between social capital and self-rated health (SRH) of the residents of Gauteng, and the impact Multiple Deprivation Poverty Index (SAMPI), a measure of area level deprivation, has on the relationship between social capital and SRH. We used retrospective data from the Quality of Life (QoL) survey conducted in 2015. A multilevel regression analysis of self-rated health (SRH) of a random sample of 27,476 individuals (after dropping none responses) aged 18 years and above, nested within 508 Wards was employed to achieve the objectives of the study. We fitted three models; Model 1 (the null model), Model 2 (regression of social capital variables and SRH) and model 3 (regression of social capital and SRH while controlling for socioeconomic and demographic variables). The median age of the respondents was 37 (Interquartile Range (IQR): 28) years. Slightly over half of the respondents (53.56%; n= 14,717/27,476) were females while the rest were males (46.44%; n= 12,759/27,476). No main effect of group membership (Adjusted OR (AOR): 1: 95% CI: 0.87-1.56) and registered to vote (AOR: 0.95; 95% CI: 0.82-1.10) was observed. However, if respondents were positive in their perception towards safety in community, there was a positive association with SRH (AOR:1.15; 95% CI: 1.01-1.31), but a strong negative association with SRH was observed if respondents had a negative perception towards safety in community (AOR: 0.70; 95%CI: 0.62 - 0.79). Variance between wards decreased from 23% (Model 2) to 13% (model 3). A strong positive joint effect on a multiplicative scale between satisfied with safety in the community and the South African Multidimensional Poverty Index (SAMPI) was observed. While, a strong negative joint effect was observed on a multiplicative scale between dissatisfied with safety in the community and the SAMPI. Perception of the community towards safety in community is the core domain of social capital that impacts health of residents of Gauteng Province. While the impact of the interaction between the SAMPI and perception towards safety is independent of the level of the SAMPI, the direction of the interaction is dependent on whether the perception of safety is negative or positive. Variation in reporting good SRH in the study area, is explained by both individual and contextual factors. Findings of this study provide a basis for prioritizing policy formulation, programmes and interventions that increase the benefits of social capital and the resultant health benefit for a greater number of people in the study area. However, further studies are needed to further investigate the causal relationship between perception of safety in the community and SRH.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Epidemiology: Epidemiology and Biostatistics to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2020